The complete genome analysis of Crimean-Congo hemorrhagic fever virus isolated in Turkey - Ozdarendeli, Aykut; Canakoglu, Nurettin; Berber, Engin; Aydin, Kemalettin; Tonbak, Suekrue; Ertek, Mustafa; Kalkan, Ahmet (Elsevier, 2010)
Crimean-Congo hemorrhagic fever virus (CCHFV) is the causative agent of a tick-borne disease with high mortality Fates in humans. The distribution of CCHFV includes over 30 countries in Asia, the Middle East, southeastern Europe, and Africa. It was first recognized in Turkey in 2002, with an increasing number of cases reported between 2002 and 2009. Recent analysis of complete genome sequences of CCHFV isolates has revealed that the genomic plasticity of the virus is surprisingly high for an arthropod-borne virus. We have determined the complete nucleotide and deduced amino acid sequences of strain CCHFV Turkey-Kelkit06 isolated from the blood of a patient in an endemic region of Turkey in 2006. The complete sequence length of the CCHFV Turkey-Kelkit06 strain is 19,186 nt, consisting of a 1673 nt S segment, a 5364 nt M segment, and a 12,149 nt L segment. Based on the analysis of S, M, and L segments, CCHFV Turkey-Kelkit06 clustered in Group V, which represents the Europe/Turkey geographic lineage. Although glycoproteins encoded by the M gene are the most variable part of the CCHFV Turkey-Kelkit06 strain, some functional domains of the glycoproteins are well conserved. Here, we report the complete sequence and genome organization of the CCHFV Turkey-Kelkit06 strain and its phylogenetic relationship to other strains of CCHFV. Collecting data on viral sequences among isolates from CCHF epidemics may provide valuable information regarding the molecular basis of the epidemic potential of the virus. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: CCHF virus; Complete genome sequence; Strain Turkey-Kelkit06; Phylogeny